Ekstrak Binahong, Eritema, Luka EFEK EKSTRAK DAUN BINAHONG SECARA TOPIKAL TERHADAP PENURUNAN DERAJAT ERITEMA LUKA TERKONTAMINASI PADA TIKUS PUTIH GALUR WISTAR - Niko Dima K (Jurnal Keperawatan Malang, 2017)
Abstract Commonly wound care use povidone iodine 10%, but it causes irritation and it can decelerate wound healing. Binahong leaves are natural plant that can treat contamined wound because it have saponin, flavonoid, polifenol, aetheric oil, and alcaloid. This research identified the effect of binahong leaves extract topically on reducing erythema degree of contamined wound. It was a true experimental research using pre and post test control group design. This research used 24 female white rats. Samples were selected by simple random sampling to be divided into 4 groups, they are NS 0,9%, binahong leaves extract 25%, 50%, and 75%. The measuring of erythema degree was did once a day for six days. Result indicated reducing erythema degree of NS 0,9% and binahong leaves extract were significantly different (ANOVA, p<0,05). They were significantly different of reducing erythema degree between extract 25% with NS 0,9% (LSD test, p<0,05), also extract 50% with NS 0,9% (LSD test, p<0,05). But they were not significantly different of reducing erythema degree between extract 25% with extract 50% (LSD test, p>0,05) and between extract 75% with NS 0,9% (LSD test, p>0,05). The conclusion was binahong leaves extract reduce erythema degree of contamined wound. There was suggested that to do advance research to identify effect of binahong leaves extract on wound healing. Keywords: binahong, erythema, contamined wound